Efficacy and safety of continuous every‐2‐week dosing of ixekizumab over 52 weeks in patients with moderate‐to‐severe plaque psoriasis in a randomized phase III trial (IXORA‐P). (1st June 2018) - Langley, R.G.; Papp, K.; Gooderham, M.; Zhang, L.; Mallinckrodt, C.; Agada, N.; Blauvelt, A.; Foley, P.; Polzer, P.; ,
Summary: Background: Ixekizumab is an interleukin‐17A antagonist approved for treatment of moderate‐to‐severe plaque psoriasis with a recommended 160‐mg starting dose, then 80 mg every 2 weeks (Q2W) to week 12, and every 4 weeks (Q4W) thereafter. Objective: To evaluate continuous Q2W dosing over 52 weeks. Methods: In this phase III, multicentre, double‐blinded, parallel‐group trial, three ixekizumab dosing regimens were assessed for efficacy and safety at week 52 in patients with moderate‐to‐severe plaque psoriasis randomized at a 2 : 1 : 1 ratio to continuous Q2W ( n = 611), continuous Q4W ( n = 310) or dose adjustment per protocol (Q4W/Q2W, n = 306), each with a 160‐mg starting dose. Dose adjustment was determined by predefined criteria to which investigators were blinded; 72 (23?5%) patients in the Q4W/Q2W group adjusted dose. Efficacy outcomes were evaluated using logistic regression. Results: Co‐primary end points were met at week 52: Psoriasis Area and Severity Index 75 responses for Q2W and Q4W dose groups were 85·9% and 79·0%, respectively ( P = 0·006), and static patient global assessment 0/1 responses for Q2W and Q4W dose groups were 78·6% and 70·6%, respectively ( P = 0·005). Treatment‐emergent and serious adverse events were comparable across dose groups. Conclusions: Ixekizumab Q2W had higher efficacy at week 52 than ixekizumab Q4W, with no increase in safety events.